Media Sirkuit Ladder Drill Terhadap Peningkatan Kecepatan Dan Kelincahan Siswa Min 1 Bojonegoro - Nugroho Susanto; Bayu Akbar Harmono; Febriyan Dwi Cahyono; Muhammad Wahyono (JURNAL STAMINA, 2022)
Biomotor fitness and ability are aspects that must be considered. This is because if you have good fitness, your body will not experience significant fatigue. Good biomotor abilities will also make body performance easier. In addition to educating Indonesian children, education has a function to improve students' biomotor abilities and fitness. The purpose of this study was to determine the effect of training. To analyze the effect of increasing speed as a result of training and learning using the ladder drill circuit media and to analyze the effect of increased agility as a result of training and learning using the ladder drill circuit media. Based on the results of research and analysis that has been carried out, the game method or ladder drill training can improve speed and agility abilities